N -(3-methylbutyl)acetamide mediates male–male courtship in Bactrocera dorsalis through behavioral threshold modulation - Yuhua Zhang; Yaoyao Chen; Wenlong Chen; Shuyuan Xing; Xirui Jin; Yuzhe Long; Zhihang Xu; Guohua Zhong; Xin Yi (Proceedings of the National Academy of Sciences, 2026)
Male–male courtship, observed across diverse taxa, is often regarded as an evolutionary paradox. Here, we address this paradox by demonstrating that such behavior in the globally invasive pest Bactrocera dorsalis arises as a byproduct of a context-dependent shift in the mating filter. We identify N -(3-methylbutyl)acetamide (MBA) as a critical signal that accumulates under high male density and female scarcity. At a threshold amount (~ 1,800 ng), MBA broadens the male’s mating filter, lowering the acceptance threshold for potential partners, thereby elevating courtship motivation and inducing hyperactivity. This broadened filter enables males to court suboptimal but potentially available females (e.g., mated or older individuals) that would otherwise be ignored, while also incidentally triggering male–male courtship. This behavioral shift is rapidly reversible upon encounter with virgin and young females, preserving an innate preference for these optimal partners. By identifying MBA as a chemical signal of mate unavailability, we reinterpret male–male courtship as a neutral byproduct of an adjustment of the mating filter under female scarcity, a trade-off between maximizing mating opportunities and accepting the incidental cost of misdirected courtship. This work bridges behavioral ecology with physiology, offering a mechanistic framework for how social environments dynamically reshape mate acceptance thresholds.